Enhancing medical education for undergraduates: integrating virtual reality and case-based learning for shoulder joint - He, Yu; Wang, Ziliang; Sun, Nianyi; Zhao, Yinuo; Zhao, Gang; Ma, Xun; Liang, Zihui; Xia, Shenglin; Liu, Xueyong (BMC medical education, 2024)
Background The integration of Virtual Reality (VR) with Case-Based Learning (CBL) has the potential to revolutionise undergraduate medical education, particularly in complex subjects such as the anatomy and rehabilitation of the shoulder joint. This study aimed to explore the effectiveness of this innovative approach in enhancing learning outcomes and knowledge retention. Methods This study employed a parallel-group, assessor-blinded randomised controlled trial (RCT) design. A comprehensive five-week educational programme was developed, combining traditional lecture-based learning with VR-enhanced CBL. The study involved 82 undergraduate students from China Medical University, who were divided into groups receiving different combinations of VR and CBL. Student performance was evaluated through tests and questionnaires. Results In the anatomy-related courses, the integration of VR technology with CBL yielded significantly higher results (87.71 ± 5.60) compared to traditional methods (82.59 ± 6.64), with a statistically significant difference ( P < 0.05). This provides compelling evidence of VR's potential to enhance student engagement and knowledge retention. In the context of physiotherapy-related courses, however, while the test scores of the VR-combined CBL group (81.85 ± 5.99) were marginally higher than those of the traditional CBL group (79.02 ± 7.57), this difference was not statistically significant ( P > 0.05). Conclusion The present study provides preliminary evidence for the benefits of incorporating VR into medical education, particularly in anatomy. While the results are promising, further research is needed to explore the optimal integration of VR and CBL in rehabilitation studies and to assess their long-term impact on student learning and clinical performance. Trial registration The study was registered with Chinese Clinical Trials Registry (Registration Number: ChiCTR2400089295) on 05/09/2024.